The exemplifying past : a philosophy of history - Akker, Chiel van den, 1974- (Amsterdam University Press, 2018)
This book addresses a wide range of philosophical problems about history and the semantics of time. Point of departure is the distinction between events under the description of past witnesses and their contemporaries and events under the description of historians. Its main claim is that a thesis on the past is exemplified rather than being justified by the available evidence. The book will not only appeal to philosophers and historians, but to students and scholars across the humanities.